Opponents of Enemies: the Transformation of the Concept of “The Political” Carl Schmitt by Chantal Mouffe (Andamios, Revista de Investigación Social, 2014)
Our article aims to analyse the theoretical initiative of Chantal Mouffe giving a new meaning to ‘the political’ front of the consensual political rationality, supported by the liberal tradition.  Such a perspective must face the challenge of a democratic reforms established by and for the pluralism of political identities. For this purpose, is brought to scene the binomial friend/enemy of Carl Schmitt to consider its transformation into another binomial: us/them in the context of the transformation of the antagonism into agonism. Will be considered its consequences in contrast with a scenario marked by increasing moralization of the political speeches. Moralization that does nothing but hide the lack of deep political debates in front of popular democratic demands.
Keywords: Radical democracy; Antagonism; Agonism